Isolasi Dan Identifikasi Senyawa Turunan Clerodin Dari Fraksi n-Butanol Daun Leilem (Clerodendrum minahassae Teijsm. & Binn) - Winokan, Miguel J. A.; Rumampuk, Rymond J.; Pongoh, Emma J. (General Chemistry Journal, 2024)
The clerodin compound has been identified in various plants of the Clerodendrum genus, this compound has antifeedant properties. Leilem (clerodendrum minahassae Teijsm & Binn) belongs to the genus clerodendrum. Leilem is an endemic plant to North Sulawesi, which is widely used as a food ingredient and traditional medicine. This research aims to isolate and identify clerodin derivative compounds from the n-butanol fraction of leilem leaves. The stages of compound isolation were solid-liquid extraction using maceration, fractionation using the liquid-liquid extraction method, separation of chemical components using the gravity column chromatography (KKG) and thin layer chromatography (TLC) methods, so that 2.1 mg of Fm1 isolate was obtained. Compound identification using the Proton Nuclear Magnetic Resonance Spectroscopy (1H-RMI) technique. The results identified the Fm1 isolate as a clerodin derivative compound